2017
DOI: 10.2174/0929867324666170124151436
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA in Brain Development and Disorder

Abstract: We hope that extensive studies of these ncRNAs would unravel and characterize novel molecular circuits in the brain, and facilitate the development of RNA-based therapeutics for people suffering from neural disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Using GO annotation, we found that the altered genes display a variety of functionalities, such as transport, biological process, and transcription. The results are supported by previous studies (Subhramanyam andHu, 2017, Weiss, et al, 2018), indicating the importance and complexity of the biological processes and transport functions involved in PTSD. The significantly functional pathway focuses on the Rap1 signaling pathway, cAMP signaling pathway, and mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Using GO annotation, we found that the altered genes display a variety of functionalities, such as transport, biological process, and transcription. The results are supported by previous studies (Subhramanyam andHu, 2017, Weiss, et al, 2018), indicating the importance and complexity of the biological processes and transport functions involved in PTSD. The significantly functional pathway focuses on the Rap1 signaling pathway, cAMP signaling pathway, and mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Eukaryotes contain thousands of very small sRNAs of about 20 nt (miRNAs, siRNAs, piRNAs) as well as longer sRNAs of up to several hundred nucleotides (lncRNAs). Eukaryotic sRNAs are involved in various processes, and their mis-regulation can lead to various diseases as well as cancer (Hombach and Kretz, 2016; Rajan et al, 2017; Romano et al, 2017; Subhramanyam and Hu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is now accepted that the majority of the mammalian genomes are transcribed into ncRNA [ 68 ]. These RNAs, which mostly consist of long ncRNAs (lncRNAs) and small ncRNAs, are abundantly expressed in the brain, where they play a role in synaptic plasticity during development [ 69 , 70 ] as well as in memory formation [ 71 , 72 ]. In a recent study, using RNA sequencing of coding and noncoding RNAs, it was demonstrated that the expression levels of mRNAs related to neurogenesis, synaptic plasticity and calcium signalling were decreased after HFD.…”
Section: Overnutrition and Synaptic Plasticitymentioning
confidence: 99%